Discourse Analysis of Digital Hoaxes as a Critical Literacy Strategy in Indonesian Language Education - Yulian Dinihari; Endang Wiyanti; Dian Nazelliana; Zetty Karyati; Lutfi Lutfi; Wuriy Handayani (Universitas Muhammadiyah Malang, 2025)
A modern society’s response to the hoax phenomena in the information age exposes challenges to confidence, information integrity, and significant public health consequences. This study intends to help increase literacy and community resistance to the spread of hoaxes, particularly emphasising the role of critical literacy and digital literacy. This study employed a thorough and systematic qualitative descriptive approach to investigate the hoax phenomenon. There are two primary stages to this method. First, literature analysis provides the foundation for comprehending the features and consequences of incorrect information. Second, a field approach was conducted using an online survey with ten questions. A survey of 108 respondents found that efforts to enhance media literacy, rigorous education, and empower individuals to become more informed consumers. The findings of this study reveal that several sorts of hoaxes are often encountered in the digital age, each with its unique set of features. One research focus is on political hoaxes, which are frequently used to influence public opinion or harm political opponents’ reputations by spreading false claims about policies or utterances that are taken out of context. The poll results reveal that people’s critical literacy must be strengthened, particularly in information verification and news interpretation.